2023
DOI: 10.1029/2023sw003601
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Pipe to Soil Potentials From Geomagnetic Storms in Gas Pipelines in New Zealand

Tim Divett,
Malcolm Ingham,
Gemma Richardson
et al.

Abstract: Gas pipelines can experience elevated pipe to soil potentials (PSPs) during geomagnetic disturbances due to the induced geoelectric field. Gas pipeline operators use cathodic protection to keep PSPs between −0.85 and −1.2 V to prevent corrosion of the steel pipes and disbondment of the protective coating from the pipes. We have developed a model of the gas pipelines in the North Island of New Zealand to identify whether a hazard exists to these pipelines and how big this hazard is. We used a transmission line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For over 50 years, it has been well known that geomagnetically induced currents (GICs) can disrupt and endanger technologies such as power transformers (Mac Ngwira et al, 2023;Rajput et al, 2021), oil pipelines (Divett et al, 2023) and railway tracks (D. H. Boteler, 2021;Patterson et al, 2024). Early works, such as those of Albertson et al (1973), Campbell (1978) and D. H. Boteler et al (1989), have identified that these GICs occur when the magnetosphere experiences intense disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…For over 50 years, it has been well known that geomagnetically induced currents (GICs) can disrupt and endanger technologies such as power transformers (Mac Ngwira et al, 2023;Rajput et al, 2021), oil pipelines (Divett et al, 2023) and railway tracks (D. H. Boteler, 2021;Patterson et al, 2024). Early works, such as those of Albertson et al (1973), Campbell (1978) and D. H. Boteler et al (1989), have identified that these GICs occur when the magnetosphere experiences intense disturbances.…”
Section: Introductionmentioning
confidence: 99%